Photovoltaics in Sweden – Success or failure?. (June 2021) - Andersson, Johnn; Hellsmark, Hans; Sandén, Björn
Abstract: Promoting global energy transitions while stimulating domestic industrialization requires national policymaking that shapes technological innovation towards specific outcomes. Although this is inherently difficult, historical case studies may bring a better understanding of innovation dynamics and thereby guide the design of future policy interventions. The purpose of this paper is to review and analyze the emergence of Swedish photovoltaics technology from a policy perspective. Our main aim is to provide a retrospective account of historical developments, but we also derive more general insights about technological innovation and related policy challenges. The paper departs from an adapted analytical framework based on the technological innovation systems approach. Our review identifies four decades of Swedish research that has largely failed to drive domestic commercialization, the rise and fall of an industry that mainly served international markets, and a rapidly growing domestic market based on imported products. This situation is the result of mismatches and fragmentation among key innovation processes, which have not been addressed by strategic policy interventions. We suggest that policymakers should promote a full range of innovation processes and consider making innovation support subject to a payback mechanism that delivers a return on public investments even if industries and markets emerge abroad. Our study also demonstrates how the technological innovation systems approach can be extended to include the function commercialization and emphasizes the importance of paying attention to the directionality of technological innovation processes. Highlights: Swedish actors have engaged in photovoltaics research since the 1980's. Efforts to establish and sustain a domestic module industry have failed. The photovoltaics market has grown exponentially during the last decade. Key innovation processes have been mismatched and fragmented. Policymakers have failed to address problems through strategic interventions.